The firm as the locus of social comparisons: Internal labor markets versus up-or-out - Emmanuelle Auriol; Guido Friebel; Frauke Lammers (Institute for the Study of Labor (IZA), 2012)
We suggest a parsimonious dynamic agency model in which workers have status concerns. A firm is a promotion hierarchy in which a worker's status depends on past performance. We investigate the optimality of two types of promotion hierarchies: (i) internal labor markets, in which agents have a job guarantee, and (ii) up-or-out, in which agents are fired when unsuccessful. We show that up-or-out is optimal if success is difficult to achieve. When success is less hard to achieve, an internal labor market is optimal provided the payoffs associated with success are moderate. Otherwise, up-or-out is, again, optimal. These results are in line with observations from academia, law firms, investment banks and top consulting firms. Here, up-or-out dominates, while internal labor markets dominate where work is less demanding or payoffs are more compressed, for instance, because the environment is less competitive. We present some supporting evidence from academia, comparing US with French economics departments.
urn:nbn:de:101:1-201205026093
Keywords: J3; M5; L2; 330; status; promotion hierarchies; incentives; sorting; Erwerbsstatus; Erwerbsverlauf; Leistungsanreiz; Interner Arbeitsmarkt; Kündigung; Vergleich; USA; Frankreich